NAMES OF DOMESTIC BIRDS IN PHRASEOLOGICAL UNITS OF THE UKRAINIAN AND POLISH LANGUAGES - Mytsan, Dariia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article describes phraseological units of the Ukrainian and Polish languages that contain a component denoting domestic birds. Phraseological units reflect the national identity of each ethnic group and constitute its cultural heritage. Ornithonymic phraseological units arouse considerable interest among contemporary linguists. The aim of the study is to analyze the semantic features of the specified phraseological units. The relevance of this study is conditioned by the fact that zoosemisms remain insufficiently described in the linguocultural aspect to this day. Therefore, the aim of the research is to analyze the semantic features of Ukrainian and Polish phraseological units containing the names of domestic birds. The study is based on contrastive, semantic, cognitive, and linguocultural methods. The scientific novelty lies in the anthropocentric comparison of birds with humans within the framework of comparative phraseology. The results of the research may be useful and interesting for more detailed studies of phraseology in multiple languages. Based on the analyzed lexicographic sources, it is shown that both Ukrainian and Polish languages contain phraseological units with the following components denoting domestic birds: chicken (kura), hen (kwoka), rooster (kogut), goose (gęś), duck (kaczka), turkey (indyk), and peacock (pawa). The semantic meaning of such fixed expressions is predominantly related to the characterization of a person. All phraseological units were classified into groups, namely: appearance, character traits, physical characteristics, and emotional state.